Injuries about the shoulder in skiing and snowboarding - McCall, D.; Safran, M. R. (British Journal of Sports Medicine, 2009)
There has been a decrease in the overall injury rate, particularly the rate of lower-extremity injuries, for alpine skiing, with a resultant increase in the ratio of upper-extremity to lower-extremity injuries. The upper extremity is injured nearly twice as often during snowboarding than alpine skiing, with approximately half of all snowboarding injuries involving the upper extremity. Shoulder injuries are likely under-reported, as many patients seek evaluation for minor shoulder injuries with their local physicians, and not at the ski medical clinic, where most epidemiology studies obtain their data. Shoulder injuries account for 4 to 11% of all alpine skiing injuries and 22 to 41% of upper-extremity injuries. During snowboarding, shoulder injuries account for 8 to 16% of all injuries and 20 to 34% of upper-extremity injuries. Falls are the most common mechanism of shoulder injury, in addition to pole planting during skiing and aerial manoeuvres during snowboarding. Common shoulder injuries during skiing and snowboarding are rotator cuff strains, glenohumeral dislocations, acromioclavicular separations and clavicle fractures. It is still unclear, when comparing snowboarding and skiing injury data, which sport has the higher incidence of shoulder injuries. Stratifying shoulder injuries by type allows better delineation as to which sport has an increased incidence of certain injury patterns. The differing mechanisms of injury combined with distinct equipment for each sport plays a role in the type and frequency of shoulder injuries seen in these two subgroups. With the increased ratio of upper- to lower-extremity injuries during alpine skiing and the boom in popularity of snowboarding, shoulder injuries are seen with increasing frequency by those who care for alpine sport injuries. According to recent epidemiological data, only clavicle and humerus fractures have shown increased rates of incidence among alpine skiers. Over the past 30 years, there has been a general decrease in both upper- and lower-extremity injuries which can be attributed to improved designs of protective equipment, increased awareness of injury patterns and emphasis on prevention. In the future, physicians and therapists who treat this population must be comfortable and confident in their treatment algorithms to help keep skiers and snowboarders conditioned and ready for the slopes and develop strategies for the prevention of upper-extremity injuries associated with these activities.